The Study of Yoga Effects on improving Quality of Life (International Journal of Food and Nutritional Sciences, 2023)
The current study's goal is to examine how yoga affects health in New Delhi among volunteers who are generally healthy and of average age (age range, 30 to 60). variables and assessments of life quality. The survey received 50 responses, of which 26 came from the control group and 26 from the yoga practice group. The Shapiro-Wilk tests for normality showed that all of the data variables were normal, indicating that the data were distributed normally. Yoga and control groups were contrasted using a paired "T" test, and the between-group effect was examined using an independent samples "T" test. In comparison to a control group, the current study assessed the effect of yoga on a number of participant's quality of life indicators. The yoga group outperformed the control group on all facets of the QOL rating scale: physicalrole , mental wellbeing, communal relationships, and public health. Hence, frequent practice of a simple and fundamental yoga technique enhances quality of life.